WAYS TO USE RESOURCES RATIONALLY IN AGRICULTURE (World Bulletin of Management and Law, 2026)
This article analyzes the essence of agriculture in sustainable economic development and the main aspects of rational use of resources in it, considers its main types. Also, the specific features of modern technologies in agriculture are studied. At the end of the work, conclusions and recommendations on the topic are formulated.